El documental Máxima y la crisis global de la Pachamama - Rodriguez, Carla Beatriz (2025)
This study exposes the problems of deterritorialization, contamination and violence faced by many peasant communities due to the state and multinational companies that invest in projects for the extraction of natural resources. The study is based on the documentary Máxima (2019) produced by Claudia Sparrow, which shows the struggles of a peasant woman who fights to protect her home, land, family, and survival. The large financial corporations, in this case Newman Corporation, one of the largest gold mining companies in the world, and supported by the Peruvian State, act with repression and violence. Given these conditions, the crisis of the global coloniality of Eurocentric power is observed in the levels of socioeconomic power in counterpoint to the practice of Buen vivir and ecofeminism, with which Máxima Acuña and her community continue to resist.